Migration : a world history - Fisher, Michael Herbert, 1950- (Oxford ; New York : Oxford University Press, USA, 2014)
"Fisher explores the process of migration chronologically and at levels varying from the migration of an individual community, to larger patterns of the collective movements of major ethnic groups, to the more abstract study of emigration, migration, and immigration. By highlighting an exemplary migration for each of the six chapters, the volume considers how technology, environment, and politics have shaped the diverse history of human migration"--
Machine generated contents note: -- Series Editors' Preface -- Preface: Migration in World History and as World History -- 1. Earliest Human Migrations: ca. 200,000 BCE to ca. 600 CE -- 2. Mixing and Clashing Migrations, 600 CE to 1450 -- 3. Migrations Start to Reconnect the World, 1450 to 1750 -- 4. National and International Migrations, 1750 to 1914 -- 5. Migrations in an Age of Globalization, 1914 to the Present -- Chronology -- Notes -- Further Reading -- Websites -- Index.
Includes bibliographical references and index.
Keywords: Emigration and immigration -- History; Migration, Internal -- History; HISTORY / Modern / General; HISTORY / Social History